A case report and literature review: one case of ceftriaxone sodium-induced reversible gallbladder stone - Luo, Changqin; He, Qingmin; Yang, Xiaocui (Frontiers in Medicine, 2024)
This paper reports a case of pseudolithiasis caused by the use of ceftriaxone sodium. The patient, a 54-year-old female, presented with intermittent abdominal pain and distension for 1 month. Initial ultrasonography showed no abnormalities. However, after receiving ceftriaxone sodium treatment for an upper respiratory tract infection, she developed discomfort in the right upper abdomen. A CT scan subsequently diagnosed her with gallbladder stones. Six weeks after discontinuing the medication, a follow-up examination revealed the disappearance of the stones, confirming the diagnosis of drug-induced pseudolithiasis. Through a literature review, this paper summarizes the mechanism, clinical manifestations, diagnostic methods, and treatment recommendations of ceftriaxone sodium-induced pseudolithiasis, providing a reference for clinical safe medication use.